2017
DOI: 10.1016/j.ijpe.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium evolution in a two-echelon supply chain with financially constrained retailers: The impact of equity financing

Abstract: This paper considers a two-echelon supply chain that has a supplier and two capital constrained retailers and in which the retailers compete in a Cournot fashion. We study the impact of external financing on the players' optimal decisions and supply chain performance. We show that as competition intensity increases, the supplier (as the Stackelberg leader) may consider merging with one retailer to avoid double marginalization. Yet, the deselected retailer may utilize external financing to return to the supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Our study differs from that of Yang et al. () in that we examine a different supply chain structure, that is, characterized by co‐opetition and dual channel.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…Our study differs from that of Yang et al. () in that we examine a different supply chain structure, that is, characterized by co‐opetition and dual channel.…”
Section: Literature Reviewmentioning
confidence: 88%
“…This branch of literature aims to provide a rationale for trade credit from various perspectives (Li et al., ; Peura et al., ; Tang et al., ; Xiao et al., ; Zhang et al., ; Wu et al., ). Several papers point out that trade credit has the advantage of risk sharing and consequently mitigating double marginalization compared with bank loan (Jing et al., ; Kouvelis and Zhao, ; Cai et al., ; Jing and Seidmann, ; Yang et al., ; Tang et al., ; Yang et al., ; Jin et al., ; Yang and Birge, ). A number of studies reveal that trade credit could be used to coordinate the capital‐constrained supply chain (Lee and Rhee, , ; Xiao et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, most literature focuses on the comparison between internal financing and external financing. Some literature points out that trade credit has more advantages than bank loans, as trade credit can alleviate double marginalization (Tang et al [22]; Yang et al [33]; Yang and Birge [34]). Kouvelis and Zhao [12] showed that trade credit is one of the important short-term financing sources among enterprises.…”
Section: (Communicated By Ada Che)mentioning
confidence: 99%
“…To improve supply chain performance, the dominant party with full capital offers trade credit to the capital-constrained party. More recently, trade credit has been widely employed as a short-term financing source to address capital constraints in supply chains (e.g., see [4,11,16,20,33,35]). Goyal [10] initially develops an EOQ model with the permissible delay in payment.…”
Section: Introductionmentioning
confidence: 99%